CONTRASTIVE ANALYSIS OF PHONEME CHANGES IN THE REDUPLICATION PROCESS IN JAPANESE AND SUNDANESE REDUPLICATION - Rama Ulun Sundasewu (Indonesian Journal of Learning and Instruction, 2025)
This study was conducted by contrasting or analyzing the similarities and differences in phoneme changes in Japanese-Sundanese Reduplication. This research aims to determine the similarities and differences in Vowel and consonant phoneme changes from the reduplication process of both languages. This research is a qualitative study with a descriptive contrastive analysis. The objects of this research are vowel and consonant phonemes that run into changes in the Japanese-Sundanese reduplication process. The results of this study indicate that vowel changes in the reduplication process do not have similarities, while the differences are generally that not all nouns, verbs, adjectives, and adverbs in Japanese can be reduplicated, whereas, in Sundanese, they can. In the reduplication process, vowel phonemes in Japanese do not run into phoneme changes, whereas in Sundanese, changes occur in the first and second vowels of the base word. For the comparison of consonant changes, Japanese-Sundanese has similarities, namely, the consonants /r/, /n/, and /m/ in Japanese-Sundanese do not run into phoneme changes, while the differences are that in Japanese, consonant phoneme changes occur at the initial phoneme, whereas in Sundanese, consonant phonemes do not run into changes.